The DTC (difference of tangentially convex functions) programming: optimality conditions - Mashkoorzadeh, F.; Movahedian, N.; Nobakhtian, S. (TOP, 2022)
We focus on optimality conditions for an important class of nonconvex and nonsmooth optimization problems, where the objective and constraint functions are presented as a difference of two tangentially convex functions. The main contribution of this paper is to clarify several kinds of stationary solutions and their relations, and establish local optimality conditions with a nonconvex feasible set. Finally, several examples are given to illustrate the effectiveness of the obtained results.